Pemasangan Zinc Anoda Protection (ZAP) sebagai Perlindungan Aktif Korosi pada Kapal - Benny Hartanto; Salim Salim (Majalah Ilmiah Bahari Jogja, 2023)
Ship maintenance is necessary and must be implemented. Among maintenance is corrosion prevention. The corrosion of a ship cannot be eliminated, but can only be reduced to a level of malignancy. There are two types of corrosion prevention, namely passive and active prevention. Passive prevention that is commonly done is by painting, while active prevention is by installing Zinc Anode Protection (ZAP). The need for ZAP on the ship depends on the wet surface area of ​​the ship, the replacement period, the type of material from the ZAP, and the size of the ZAP. Installation of ZAP on a ship is generally done by bolting it on the ship's body. The distance between one plate and another is not the same. Placement of ZAP is installed in relatively large flow sections around the keel and those located in the eddy area around the propellerinstalled tighter than other areas.